1993
DOI: 10.1136/jnnp.56.2.194
|View full text |Cite
|
Sign up to set email alerts
|

MRI-pathological correlate of brain lesions in a necropsy case of HTLV-I associated myelopathy.

Abstract: A postmortem case of HTLV-I associated myelopathy (HAM)/tropical spastic paraparesis (TSP) with a history of remission and exacerbation of neurological signs and symptoms, resembling those ofmultiple sclerosis is reported. MRI analysis revealed lesions in the periventricular white matter in addition to atrophy of the thoracic spinal cord, characteristic of HAMITSP. The cerebral periventricular areas consisted of ill-defined paucity of myelin sheaths with astrocytic gliosis and hyaline thickening of blood vesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
4

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 15 publications
2
19
0
4
Order By: Relevance
“…However, the paraventricular cerebral white matter showed mononuclear cell infiltration with foci of myelin pallor and gliosis. The case described by Ogata et al 10 had an evolution of 36 years and, neuropathologically, showed a severe atrophy of the lower thoracic spinal cord, a loss of myelin and axons in the lateral column and, to a lesser degree, in the posterior column, posterior spinocerebellar tract and the anterior funiculus. Moreover, hyaline thickening of the blood vessels of the thoracic spinal cord and astrocytosis were seen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the paraventricular cerebral white matter showed mononuclear cell infiltration with foci of myelin pallor and gliosis. The case described by Ogata et al 10 had an evolution of 36 years and, neuropathologically, showed a severe atrophy of the lower thoracic spinal cord, a loss of myelin and axons in the lateral column and, to a lesser degree, in the posterior column, posterior spinocerebellar tract and the anterior funiculus. Moreover, hyaline thickening of the blood vessels of the thoracic spinal cord and astrocytosis were seen.…”
Section: Discussionmentioning
confidence: 99%
“…The autopsied cases of long evolution are very few in the literature 8,[10][11][12]15,17 . The two Iwasaki's 8 cases of long evolution (19 and 28 years, respectively) were typical clinical TSP/HAM and, neuropathologically, "neither lymphocytic nor monocytic cell infiltration was seen in markedly devastated and shrunken parenchymal tissues".…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors explained the absence of inflammatory infiltration by the use of corticosteroids. However, autopsy studies show that inflammatory changes are perivascular infiltration, rarely occurred activated T lymphocytes, as well as damage in the parenchyma 25 . In this study, no significant associations between the presence and location of white matter lesions on brain MRI and duration of illness or disability were found.…”
Section: Discussionmentioning
confidence: 99%
“…However, as patients were matched by the same age, the high frequency of white matter lesions on MRI in both groups could be related to demyelination secondary to degenerative microangiopathy. Kira et al and Ogata et al demonstrated, through MRI and autopsy, correlation between the periventricular white matter lesions and cerebral spinal posterior column 24,25 . The study revealed similar pathologic changes to the brain and spinal cord, with demyelination, loss of axons and thickening of small vessels.…”
Section: Discussionmentioning
confidence: 99%